Design of PKN learning model based on tolaki local wisdom to improve prosocial behavior - Rusmin, Lisnawati; Reni, Waode (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Design of a Learning Model Based on Tolaki Local Wisdom to Improve Prosocial Behavior. This research is a Research and development (R&D) research that aims to design a learning model based on local wisdom of Tolaki to improve Prosocial behavior. This type of research is Research and development (R&D) research by adopting a 4D model developed by Thiagarajan, with data collection techniques through interviews, questionnaires, observations, and documentation as well as assessment sheets of feasibility, practicality, and effectiveness of products, which are further analyzed with qualitative and quantitative statistics. The results of the show that the development design in the form of learning model books and teaching guidebooks shows assessment results that are very valid or very feasible to be used to improve students' social behavior.